Fracture toughness of hot rolled pure magnesium: Correlation with microstructure and texture. Issue 1 (March 2021) - C.Prakash, Gautam; Bar, H.N.; Sivaprasad, S.; Tarafder, S.; Biswas, Somjeet
Abstract: Pure magnesium possesses high specific strength, and hence it has excellent potential for biodegradable structural bioimplants. Such a load-bearing application requires the material to have sufficient fracture toughness to sustain the presence of undesirable microcracks. In this work, biomedical grade pure magnesium was hot-rolled to obtain equiaxed microstructure with basal texture. Single edge notch bending specimens with a notch along the rolling direction, transverse direction, and 45° to both were prepared. Fatigue pre-cracking was performed, followed by the fracture toughness tests. All the samples show sufficient plasticity during the fracture toughness test to evaluate J 1 C . The characterization was done by electron backscatter diffraction. The influence of initial texture and the strain state on the evolution of twins in the vicinity of the crack path and fracture toughness was comprehended.